No exercise-associated hyponatremia found in an observational field study of male ultra-marathoners participating in a 24-hour ultra-run - Knechtle, B.; Knechtle, P.; Rosemann, T. (The Physician and Sportsmedicine, 2010)
Aims In a recent study of male ultra-marathoners who participated in a 161-km ultra-run, the prevalence of exercise-associated hyponatremia (EAH) was reported to be 50%, which is a considerably higher percentage than that seen in marathoners. We investigated the prevalence of EAH in male ultra-marathoners competing in a 24-hour run held in Basel, Switzerland. Body weight, hematocrit levels, plasma volume, plasma sodium concentration, urine specific gravity, and fluid intake were recorded in 15 male ultra-marathoners (mean age ± standard deviation [SD], 46.7 [5.8] years; plasma sodium, 71.1 [6.8] kg; height, 1.76 [0.07] m; body weight, 23.1 [1.84] kg/m2). Plasma sodium was measured at 135.3 (2.8) mmol/L before the race and remained unchanged at 135.4 (3.6) mmol/L after the race. The competitors consumed a total of 15.1 (5.1) L during the race, equal to 0.62 (0.21) L/hour. Fluid intake correlated to the mean running speed (r = -0.87; P = 0.0001). Body weight decreased significantly (P = 0.0009) by 2.2 kg. Hematocrit remained unchanged, and urine specific gravity increased significantly (P = 0.0005). Plasma volume increased by 4.9% (15.8%). Changes in body weight showed no association with post-race plasma sodium. The normal resting value should be 140 mmol/L so that a decrease of 5 mmol/L is described as EAH. Because the starting plasma sodium in this study was 135 mmol/L, it is not possible to define EAH as a value that is < 135 mmol/L. Instead, the correct definition should be a plasma sodium concentration of 130 mmol/L (ie, 5mmol/L below the normal resting value). Following this definition, it was determined that no athlete developed EAH in this 24-hour run.